Assessing Item Reliability, Differential Item Functioning, and Wright Map Analysis of the GSP122 Test at a Public University in Nigeria - Uba, Abubakar Rabiu; Khairani, Ahmad Zamri (Journal of Education For Sustainable Innovation, 2024)
This study examines the psychometric properties of the GSP122 test, an Information and Communication Technology (ICT) knowledge assessment administered at a public university in Nigeria. Despite its importance in evaluating students' ICT competencies, no prior attempt has been made to investigate the test's psychometric qualities. The research focuses on three key aspects: item reliability, Differential Item Functioning (DIF), and Wright Map analysis. The study employs Rasch analysis to evaluate these properties. A sample of 600 GSP122 test scripts was randomly selected from undergraduate students across various departments to ensure a representative assessment. Findings reveal that the test possesses strong item reliability, indicating consistency in measuring the intended construct. Furthermore, all items are found to be DIF-free, suggesting fairness across different subgroups of test-takers. The Wright Map analysis, however, indicates that the test doesn't accurately target the abilities of students at the extreme ends and bottom of the proficiency spectrum. Specifically, some items are identified as too difficult and too easy relative to the students' ability levels. These results provide valuable insights into the GSP122 test's strengths and areas for improvement. While the test demonstrates robustness in reliability and fairness, adjustments in item difficulty could enhance its effectiveness in assessing students across all proficiency levels. This comprehensive analysis contributes to the validation of the GSP122 test and offers a foundation for evidence-based refinements in ICT assessment practices within the Nigerian higher education context.